Psychological Analysis of the Constituents of the Cognitive Component of Personal Helplessness in Students’ Educational Activity - Duchyminska, Tamara (Psychological Prospects Journal, 2016)
The article analyzes the concept of helplessness and it has been grounded that pessimistic attributive style is a major risk factor of personal human helplessness. The main diagnostic criteria of formation of personal helplessness have been determined: pessimistic attributive style, low self-esteem and personality concentration on own negative emotional states, low motivation of achievements and level of subjectivecontrol. The researched groups with high level of helplessness and its opposite characteristics – independence have been selected. It has been revealed that cognitive component of helplessness manifests itself in pessimistic perception of negative events (failures), explaining their appearance by persistent and global causes (generalization of failures), high level of failures personalization and is supplemented byother characteristics of cognitive sphere of “helplessness” students: unreality in actions and relations, lack of flexibility, practical mindset, high sensitivity to failures and mistakes, etc. The interrelation of indicators of cognitive component of helplessness withmotivational characteristics of personality of student has been empirically confirmed. It is revealed that pessimistic attributive style is combined with low need to achievement, low desire level to knowledge and cognitive activity and low educational achievement. Students with high level of personal helplessness inherent low achievement motive, lowered intrinsic motivation of study, severity of anxiety andanger as the dominant emotional states in the process of educational activity.Keywords: personal helplessness, theory of causal attribution, pessimistic attributive style, motivation of educational activity.